Flour and bread making properties of whole and split yellow peas treated with dry and steam heat used as premilling treatment. Issue 6 (17th October 2020) - Sopiwnyk, Elaine; Bourré, Lindsay; Young, Gina; Borsuk, Yulia; Lagassé, Shelley; Boyd, Lindsey; Sarkar, Ashok; Jones, Stuart; Dyck, Adam; Malcolmson, Linda
Abstract: Background and objectives: Pulse flours can impart off‐flavors limiting their use in foods. The objective of this study was to examine the flour and bread making properties of whole and split yellow peas treated with dry and steam heat used as a premilling treatment. Findings: Particle size distributions and pasting properties of flours milled from heat‐treated peas were altered, and starch damage was reduced compared to flours milled from untreated peas. Breads made with flour milled from heat‐treated peas had similar firmness to breads made with flour milled from untreated peas with no change in volume and minimal impact on crumb structure. Changes in crumb color (lower L *, higher a *) were consistent with color changes observed in the flours. Heat treating whole peas produced breads with decreased aroma, flavor, and aftertaste, whereas heat treating split peas produced breads with lower intensities of aroma, flavor, bitterness, and aftertaste and increased acceptability. Conclusions: Revtech dry and steam heating of whole and split yellow peas as a premilling treatment successfully reduced off‐flavors with minimal changes to flour and bread making properties. Significance and novelty: Heat treating pulses prior to milling offers greater opportunities for incorporating pulse flours in foods.